Does Friday-Monday Dance with Harmony? - Asnawi, Said Kelana; Wijaya, Chandra; Siagian, Dergibson; Alzah, Salam Fadillah (LPPM Universitas Terbuka, 2021)
This research is about the weekend effect, a combination of Friday and Monday, and its impact on Monday trading volume. It was found that there was no association between Friday return and Monday return. Still, they occur a combination both Friday and Monday negative return was more than combination both Friday and Monday positive return. There are both combinations (Friday and Monday), and price fluctuation has not affected Monday's volume. There is also no difference in characteristics between groups: Friday and Monday negative return and Friday and Monday positive return. Thus, Friday-Monday dances with harmony; the efficient market occurs. Keywords: Weekend Effect; Trading Volume; Liquidity; Risk-Return; Market Efficient